Pengelasan atribut kualiti bagi meningkatkan kepuasan pelanggan - Wan Norsiah Mohamed,; Faridatulazna A. Shahabuddin,; Zainol Hj. Mustafa, (Penerbit ukm, 2007)

(untitled)
Customer satisfaction is crucial for future business success. Various techniques have been used by researchers and practicioners to prioritise the effort in meeting customers’ needs. Importance Performance Analysis (IPA) is seen as a simple and an effective technique. However, there is growing evidence that quality factors can be classified into three different categories based on their effects on customer satisfaction, as suggested by Kano’s Model. Some of the relationships have been proven as nonlinear. The applicability of IPA, which assumes linear relationship between performance of quality factors and satisfaction, is called into question. In this paper, the nature of relationship between performance of quality factors and satisfaction is examined. Managerial implications derived from IPA and Kano’s model are compared